Adolescent nicotine induces persisting changes in development of neural connectivity. (August 2015) - Smith, Robert F.; McDonald, Craig G.; Bergstrom, Hadley C.; Ehlinger, Daniel G.; Brielmaier, Jennifer M.
Highlights: Adolescent nicotine induces persisting age-specific dendritic structure changes in several areas of CNS. Observed dendritic and spine changes imply new synapses and altered connectivity. Dendritic changes are accompanied by persisting functional changes. Connectivity alteration in CNS may represent a new hazard of adolescent nicotine. Abstract: Adolescent nicotine induces persisting changes in development of neural connectivity. A large number of brain changes occur during adolescence as the CNS matures. These changes suggest that the adolescent brain may still be susceptible to developmental alterations by substances which impact its growth. Here we review recent studies on adolescent nicotine which show that the adolescent brain is differentially sensitive to nicotine-induced alterations in dendritic elaboration, in several brain areas associated with processing reinforcement and emotion, specifically including nucleus accumbens, medial prefrontal cortex, basolateral amygdala, bed nucleus of the stria terminalis, and dentate gyrus. Both sensitivity to nicotine, and specific areas responding to nicotine, differ between adolescent and adult rats, and dendritic changes in response to adolescent nicotine persist into adulthood. Areas sensitive to, and not sensitive to, structural remodeling induced by adolescent nicotine suggest that the remodeling generally corresponds to the extended amygdala. Evidence suggests that dendritic remodeling is accompanied by persisting changes in synaptic connectivity. Modeling, electrophysiological, neurochemical, and behavioral data are consistent with the implication of our anatomical studies showing that adolescent nicotine induces persisting changes in neural connectivity. Emerging data thus suggest that early adolescence is a period when nicotine consumption, presumably mediated by nicotine-elicited changes in patterns of synaptic activity, can sculpt late brain development, with consequent effects on synaptic interconnection patterns and behavior regulation. Adolescent nicotine may induce a more addiction-prone phenotype, and the structures altered by nicotine also subserve some emotional and cognitive functions, which may also be altered. We suggest that dendritic elaboration and associated changes are mediated by activity-dependent synaptogenesis, acting in part through D1DR receptors, in a network activated by nicotine. The adolescent nicotine effects reviewed here suggest that modification of late CNS development constitutes a hazard of adolescent nicotine use.